1979
DOI: 10.1007/bf01917915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on immunological phagocytosis by macrophages

Abstract: It was shown that, in physiological concentrations, insulin enhances, in vitro, the immunological phagocytosis of sensitized sheep erythrocytes by cultured mouse peritoneal macrophages. Insulin seems to stimulate macrophage phagocytosis as a cholinomimetic agonist by increasing the intracellular levels of cyclic GMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…When Lima etal. [137] used insulin in physiological doses (10 -9 to 10 -a3 mol/1), they found enhancement of phagocytic responses by murine peritoneal macrophages, a result confirmed by Kragballe et al [138] using human monocytes. Using a different assay Bar et al [139] reported inhibition of antibody-dependent cellular cytotoxicity by insulin (10 -1~ mol/1), but the inhibition was not dramatic (about 30%).…”
Section: Effects Of Insulin On In Vitro Immune Functionmentioning
confidence: 68%
See 1 more Smart Citation
“…When Lima etal. [137] used insulin in physiological doses (10 -9 to 10 -a3 mol/1), they found enhancement of phagocytic responses by murine peritoneal macrophages, a result confirmed by Kragballe et al [138] using human monocytes. Using a different assay Bar et al [139] reported inhibition of antibody-dependent cellular cytotoxicity by insulin (10 -1~ mol/1), but the inhibition was not dramatic (about 30%).…”
Section: Effects Of Insulin On In Vitro Immune Functionmentioning
confidence: 68%
“…Further evidence that insulin can affect the function of the immune system comes from a variety of in vitro experiments (Table6) [136][137][138][139][140][141][142][143][144][145][146][147][148]. Rhodes [136] reported that insulin inhibited the expression of Fc receptors on guinea pig macrophages as measured by an erythrocyteantibody rosetting assay, but the concentration of insulin employed was in the 5 x 10 -5 mol/1 range; this is three to seven orders of magnitude larger than the concentration commonly regarded as physiological [137][138][139]. Similarly, Hunt and Eardley [148] reported inhibition of antibody formation and Interleukin-2-induced proliferation by these concentrations of insulin.…”
Section: Effects Of Insulin On In Vitro Immune Functionmentioning
confidence: 99%
“…It is known that TB affects the production of insulin and that it is detrimental to insulin sensitivity [ 71 ]. Although several studies have shown the role of insulin in cellular metabolism and phagocytosis of M. tuberculosis, little is known about insulin resistance as a potential risk factor for active TB [ 72 , 73 ]. Chao et al investigated the immunological mechanisms underlying the susceptibility of diabetic patients to TB [ 74 ].…”
Section: Sensitivity Of Asian People With Dm To Tbmentioning
confidence: 99%
“…The phagocytic activity is low in type 2 diabetes and improves after metabolic improvement [71]. Insulin inhibits phagocytosis of normal human neutrophils [72]. It also enhances immunological phagocytosis by macrophages [72].…”
Section: Peptide Hormonesmentioning
confidence: 99%
“…Insulin inhibits phagocytosis of normal human neutrophils [72]. It also enhances immunological phagocytosis by macrophages [72]. Glucagon and somatostatin stimulated macrophage phagocytosis [70].…”
Section: Peptide Hormonesmentioning
confidence: 99%